PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL (Studi pada Pemerintah Kabupaten/Kota di Jawa Tengah) - Deva Yoga Permana; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
This study aims to provide empirical evidence about the effect of the Economic Growth, Local Own Revenue (PAD), the General Allocation Fund (DAU) and Specific Allocation Fund (DAK) on the Capital Expenditure districts / cities in Central Java. The sample used in this study were 35 districts / cities in Central Java taken from the Report of Actual Income and Expenditure Budget (budget) from the years 2007-2009. Methods of data collection used in this study is whole population census methods. Analysis tool used in this study is multiple linier regression with a t test, f test, and test the coefficient of determination. The results of this study indicate that partial Local Own Revenue (PAD) and the General Allocation Fund (DAU) have a significant effect on the Capital Expenditure. Meanwhile, Economic Growth and Specific Allocation Fund (DAK) had no significant effect on the Capital Expenditure. Simultaneously Economic Growth, Local Own Revenue (PAD), the General Allocation Fund (DAU) and Special Allocation Fund (DAK) significant effect on the Capital Expenditure.